Consequences of Workplace Bullying From Nurses' Perspectives: A Qualitative Descriptive Study in Iran - Saeedeh Piri; Rostam Jalali; Alireza Khatony (Wiley, 2024)
ABSTRACT Aim The aim of this study is to explore Iranian nurses' experiences regarding the consequences of bullying. Design A qualitative descriptive study is carried out using conventional content analysis and Granheim and Lundman's method. Methods Data for this study were collected through 12 in‐depth, semi‐structured individual interviews with nurses employed at a teaching hospital in REDACTED, western Iran. Purposeful sampling was employed until data saturation was achieved. Data management was conducted using MAXQDA software. Results The participants consisted of 12 nurses, with a mean age of 36.1 ± 8.6 years. Their experiences of workplace bullying were analysed and categorised into a main theme called 'Consequences of Workplace Bullying', with two categories identified as 'Organisational Consequences' and 'Individual Consequences'. The organisational consequences were further elaborated through two subcategories: 'work performance consequences' and 'patient care consequences'. The individual consequences category included subcategories including 'psychosomatic consequences', 'psychological consequences' and 'family consequences'. Conclusion Workplace bullying among nurses can have negative impacts on patients, nurses and organisations. In order to mitigate these effects, nurse managers can take proactive measures by implementing management strategies and fostering a positive work culture. By addressing the underlying factors and promoting a supportive environment, the adverse consequences of workplace bullying can be reduced or prevented. Patient or Public Contribution Yes.